Blood plasma miR‐20a‐5p expression as a potential non‐invasive diagnostic biomarker of male infertility: A pilot study. (8th June 2020) - Cito, Gianmartin; Coccia, Maria Elisabetta; Salvianti, Francesca; Fucci, Rossella; Picone, Rita; Giachini, Claudia; Cocci, Andrea; Falcone, Patrizia; Micelli, Elisabetta; Verrienti, Pierangelo; Minervini, Andrea; Carini, Marco; et al.
Abstract: Background: Recently, alterations in miRNAs expression profile in semen have been linked to damaged spermatogenesis, suggesting miRNAs could be used as potential infertility biomarkers. In previous animal studies, miR‐20a‐5p was found to be down‐expressed in low motile spermatozoa, implying its potential target of genes associated with cell apoptosis. Objective: To investigate miR‐20a‐5p expression in blood plasma of patients suffering from non‐obstructive azoospermia (NOA), compared to normozoospermic controls. Materials and Methods: Between January 2018 and December 2019, from 52 infertile couples eligible for the study, 24 couples were finally enrolled in this monocentric observational prospective pilot study. Patients were included into two groups: Group 1 comprised men with NOA (n = 14) and Group 2 fertile men partners of women with female tubal factor infertility (n = 10). All NOA patients underwent testicular sperm extraction. The expression of circulating miR‐20a‐5p in plasma samples was assessed by RT‐qPCR. A relative quantification strategy was adopted using the 2 −ΔCq method to calculate the target miR‐20a‐5p expression with respect to miR‐16‐5p as endogenous control. Results: Median blood plasma miR‐20a‐5p was significantly higher in patients affected by NOA (0.16 2 −ΔCt, range: 0.05‐0.79 2 −ΔCt ) than in fertile controls (0.06 2 −ΔCt, range: 0.04‐0.10 2 −ΔCt ), P < .001. MiR‐20a‐5p was positively correlated with follicle‐stimulating hormone (FSH) ( r rho = −0.490, P = .015) and luteinizing hormone (LH) ( r rho = −0.462, P = .023), and negatively correlated with serum total testosterone (TT) ( r rho = −0.534, P = .007) and right and left testicular size ( r rho = −0.473, P = .020 and r rho = −0.471, P = .020, respectively). Successful sperm retrieval (SR) rate was 50.0%. Median value of miR‐20a‐5p did not differ significantly among patients with successful SR and those with negative SR. Testicular histological examination showed: hypospermatogenesis in 6/14 (42.8%), maturation arrest in 4/14 (28.6%), sertoli cell‐only syndrome in 4/14 (28.6%). No significant differences in miR‐20a‐5p were found between histopathological patterns ( P > .05). Conclusions: MiR‐20a‐5p could represent a novel non‐invasive diagnostic biomarker of male infertility.